Clinico hematological profile and outcome of anemia in children at tertiary care hospital, Karimnagar, Telangana, India - Madoori, Srinivas; C., Ramya; Valugula, Shashidhar; G., Sandeep; Kotla, Sreenivas (International Journal of Research in Medical Sciences, 2017)
Background: Anemia is a common health problem worldwide. It is an important cause of morbidity and mortality of young and growing children in rural areas of developing countries. Young growing anemic children have various clinical symptoms, pallor, Jaundice, fever, cough, breathlessness, hyper pigmentation, tremors, and hepatosplenomegaly. The main objective is to study the clinical and haematological profile and variants of anemia in children of age 2 months to 14 years admitted in tertiary care hospital, Karimnagar. Methods: A retrospective study was carried out by studying medical records of hospital attached to Chalmeda Institute of Medical Sciences, Karimnagar between January 2010 to December 2014. Study population constitutes total number of 316 cases of anemia in children of age 2 months to 14 years admitted in tertiary care hospital of Karimnagar. Diagnosis of anemia was based on hemoglobin levels and on the basis of clinical presentations. Classification of anemia was done by clinical findings, complete blood picture with peripheral smear and hemoglobin electrophoresis. Results: In present study out of 316 cases, 173 were males and 143 were females. It was found that 58% of children were anemic due to iron deficiency anemia, 27 % were having sickle cell disorder, 9 % were having Thalassemia, and 5 % with megaloblastic anemia and 2% with aplastic anemia. Conclusions: Besides haematological investigations for typing of anemia, Haemoglobin electrophoresis establishes the disease in haemoglobinopathies. Adequate health and healthy nutritional habits and prescription of Iron supplements are of great importance in prevention and management of anemia in children assisted by public health services.